Effect of goal-directed fluid therapy on perioperative microcirculatory perfusion in elderly patients undergoing surgery - QIU Yanli, ZHU Qianlin, LUO Yan (Waike lilun yu shijian)
With the increasing number of elderly surgical patients, anesthesiologists are confronted with greater challenges. Given the close association between perioperative microcirculatory perfusion and health outcomes in geriatric populations, this article explored the impact of emerging goal-directed fluid therapy (GDFT) on microcirculatory perfusion in elderly surgical patients, aiming to provide new insights for optimizing clinical practice.